DEVELOPMENT OF PRE-SERVICE FOREIGN LANGUAGES TEACHERS' EMOTIONAL INTELLIGENCE BY MEANS OF REFLECTION - Iryna Zadorozhna; Olha Datskiv; Nataliia Levchyk (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2018)
The purpose of this paper is to investigate the development of pre-service foreign languages teachers' emotional intelligence by means of reflection. 70 students of Ternopil Volodymyr Hnatiuk National Pedagogical University, Department of Foreign Languages, participated in the study for four years. Among them, there were 67 females and 3 males aged 18 to 26. Research instruments used in the study are Self-Rated Emotional Intelligence Scale and Reflection in Learning Scale. Following the completion of these self-rated questionnaires in the first semester of their programme, the participants were engaged in reflective practice by means of three reflective tools - writing journals, reflective portfolios and reflective classroom discussions. Five domains of emotional intelligence (perceiving, using, understanding, managing emotions and social management) became an integral part of reflection. It was hypothesised that a relationship between emotional intelligence and reflective practice would emerge. At the end of the eighth semester, the participants self-assessed their emotional intelligence and reflective skills again using the same instruments. Results indicate that systematic reflection develops pre-service foreign languages teachers' emotional intelligence. In addition, classroom discussions revealed the need for reflection in a foreign language for personal and professional development of the participants. We conclude that there is a relationship between the level of pre-service foreign languages teachers' emotional intelligence and the development of their reflective skills. The findings of the study can be applied in the design and implementation of educational programmes for pre-service foreign languages teachers.